Philosophical heritage of the turkic peoples. Sacred animals in the life of turkic world, in Kazakhstan and Kyrgyzstan - Fishler, A. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
The article provides a philosophical analysis of famous Kazakh and Kyrgyz poets and writers on the theme of their reflection in their work of the specifics of the Scythian and Turkic culture of "animalism". The author asks why animals are so sacred in the Turkic world? How are sacred animals represented in Scythian and Turkic art? One of the hypotheses is that the open-air distance steppe, sung by local poets, is something other than closed spaces of European civilization. And the animals here have always served people as favorite companions in the long nomads and connects it with the natural world, which made his life the most harmonious. In such historical conditions described by Abay, Ch. Aitmatov, O. Suleimenov, M. Auezov and others, animals acquire symbolic concepts of strength, endurance and loyalty. Key words: sacred animals, Scythians, Turks, steppe creativity, symbols.